Demographic factors associated with alcohol use among young men in rural areas of Sarawak - Amit, Noh; Hasking, Penelope; Manderson, Lenore (Routledge, 2013)
Little research has been conducted on alcohol use in developing countries, particularly where attitudes towards alcohol differ among ethnic groups. We examine patterns of alcohol use and the relationships between religion, ethnicity, age, and employment; and alcohol use among young men in East Malaysia, among whom drinking might be expected to differ for social, economic, and religious reasons. The participants were self-selected from rural villages in Kuching and Samarahan Districts, Sarawak. Data were collected from 161 participants of Iban, Bidayuh, and Malay ethnicity, aged 18–30years, using an anonymous self-report questionnaire. Christian participants (both Iban and Bidayuh) were more likely to drink than Malay Muslim participants, with Iban participants reporting the highest alcohol use. Participants who were unemployed or employed in the private sector reported drinking more than participants employed in the civil service. The interaction between age and religion in predicting alcohol use indicated that regardless of religious affiliation, participants’ alcohol consumption increased when they were in their mid 20 s and decreased in their late 20 s, with the difference between Christian and Muslim participants most evident among men aged 22–25 years. The interaction between age and ethnicity in predicting alcohol use indicated that Malays tended to decrease their use of alcohol with age, while Iban participants tended to increase alcohol consumption with age. Among Bidayuh, alcohol use increased during their early 20 s and decreased in their mid-20 s; this was followed by a relative increase in use again in their late 20 s.The findings of this study corroborate previous research associating demographic factors and alcohol use. However, we also observed that although few Malay participants drank, those who did were less likely to drink in a low-risk pattern than Christian participants, and more likely to drink in a hazardous than low-risk fashion.